Association between C reactive protein level and depressive symptoms in an elderly Korean population: Korean Social Life, Health and Aging Project. Issue 2 (23rd February 2015) - Song, Bo Mi; Lee, Ju-Mi; Choi, Wungrak; Youm, Yoosik; Chu, Sang Hui; Park, Yeong-Ran; Kim, Hyeon Chang
Abstract : Objective: The relationship between inflammatory markers and depressive symptoms has been reported inconsistently. Moreover, there were only a few studies conducted in an Asian population. The purpose of this study was to examine the association between C reactive protein (CRP) and depressive symptoms in an elderly Korean population. Design, setting and participants: This study used data from the Korean Social Life, Health and Aging Project Health Examination Cohort, which started in 2011. Among participants aged 60 or over recruited from a rural community, 569 (224 men and 345 women) without a history of stroke, angina pectoris, myocardial infarction or CRP≥20 mg/L were employed for cross-sectional analyses. As a marker of systemic inflammation, CRP was measured. Depressive symptoms were measured with the Center for Epidemiologic Studies Depression (CES-D) scale. Multiple linear regression analysis was used to investigate the relationship between CRP and depressive symptoms. Results: In men, CRP levels had significant associations with depressive symptoms before (β=0.420, p=0.010) and after (β=0.336, p=0.025) adjusting for age, body mass index, systolic blood pressure, number of comorbidities, smoking status, alcohol intake, marital status, education and sleep duration. However, in women, the association between CRP and depressive symptoms was not significant before (p=0.250) and after (p=0.256) adjustment. Conclusions: Our findings suggest that elevated CRP levels are independently associated with the presence of depressive symptoms in elderly Korean men.